NOWE STANOWISKO SOPLÓWKI BUKOWEJ HERICIUM CORALLOIDES (Scop.) Pers. w WIELKOPOLSCE - Kujawa, Anna; Konik, Judyta (Badania Fizjograficzne Seria B - Botanika, 2020)
The paper presents a new locality of the protected fungus Hericium coralloides located in a manorial park in Turew. Nine basiodiocarps grew on a fragment of trunk of Ulmus sp. lying at the alley. The described locality is the fourth known in Wielkopolska region.